MENINGKATKAN KEMAMPUAN MENGENAL KONSEP Bilangan MELALUI MEDIA GAMBAR PADA ANAK KELOMPOK A TK ISLAM AL-IKHLAS KECAMATAN BANGKO - Mazniah Mazniah; Zulkifli Zulkifli; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : Still less increasing children's ability to recognize the concept of the number of children aged 4-5 years and some children can not even mention the numbers 1 to 10 and have not been able to recognize numbers 1 to 10 is the background of this research belakagi. To optimize the child's ability to recognize the concept of numbers is one of the attempts to use the media image. Aims to optimize the ability to recognize the concept of the number of children aged 4-5 years through media images are provided. This type of research with the class action sobjek 10 children. This research was conducted in two cycles. It can be concluded that from the first cycle to the second cycle of children's ability to know the concept of numbers have increased quite means. Improvement occurred, ie from before the action to the first cycle of 31.43% the first cycle to the second cycle of 34.04%, and increased from the prior cycle to cycle II of 76.17%. From the results of these studies concluded that through the ability to recognize the concept of numbers by media images may improve the ability to know the concept of the number of children aged 4-5 years in group A TK Islam Al-Ikhlas District of Bangko Rokan Hilir.Keywords: Concepts of Numbers, Childhood, Media Image